High-temperature oxidation of Cr-coated laser beam welds made from E110 zirconium alloy. (February 2022) - Sidelev, D.V.; Kashkarov, E.B.; Grudinin, V.A.; Krinitcyn, M.G.
Abstract: The effect of chromium coating on oxidation performance of laser beam welds (LBW) from E110 zirconium alloy was studied. Oxidation tests were performed in air under temperature ramp from 500 to 1100 °C and isothermal treatment for 2 and 10 min. The uncoated LBW alloy demonstrate unstable local oxidation in the weld region, while heat-affected and bulk zones were characterized by higher oxidation resistance. The Cr coating prevents oxidation of LBW E110 alloy at high temperature. The mechanical properties of the alloy did not deteriorate after oxidation. Some effects of laser beam welding on E110 alloy oxidation were discussed. Highlights: Accelerated air oxidation of laser beam weld of E110 alloy at 1100 °C. 8 µm-thick Cr coating prevents oxidation of laser beam welded E110 alloy. Hardness of Cr-coated welded alloy does not deteriorate after oxidation.